Impact of Using Automatic Smart Control Technology Using UV Rays on Hydroponic Chili Plants - Satria, Habib; Aldhi, Muhammad; Susilawati, Susilawati; Irwandi, Putra; Ridha, Arrazy Elba (LPPM Universitas Andalas, 2023)
The rapid development of time has reduced the land used by farmers for farming due to development. For that, design a hydroponic system to minimize the land. Chili hydroponic plants are a type of vegetable that has many benefits and is liked by many people. So that hydroponic chili cultivators can produce optimal harvests, a tool is designed using automatic smart control technology using UV lamps. The findings in the field are that there are several steps that must be taken so that hydroponic plants can be more optimal in the results of chili cultivation. The first step is to design a smart plant control automatic tool, then use several sensors including EC sensors, ph sensors, RTC sensors, and ultraviolet lamps. An initial study of the potential benefits to be gained by partners or chili farmers based on the results of field testing is that this technology can maximize harvest time efficiency from manual hydroponic cultivation, which was originally 90 days to 70-80 days. Therefore, the automatic smart plant control system using UV lamps has a harvest speed of 70-80 days, while the manual method can reach 90 days. Thus, it is hoped that the economy of chili cultivators will increase if the smart plant control automatic system is used.